THE RELEVANCE OF INTEGRAVASF IN SOCIAL DENTISTRY IN PROMOTING HEALTH IN THE SÃO FRANCISCO VALLEY - Ribeiro Lacerda, Anne Caroline; Mendes Amancio, Carollina; Guerra da Cunha Souza, Julyana; Rocha Tavares, Larissa; de Souza Pereira, Malvina; França Antunes, Maria Alice; Jaqueline Caldas Pionorio , Sara; Noemi Granja Rodrigues, Séfora; Gomes Pereira, Wellida; Carvalho Ribeiro, Maria Eduarda (Health and Society, 2024)
The IntegraVasf Social Project is relevant in promoting oral health in the São Francisco River Valley, highlighting the health area. This analysis is based on a study focused on dentistry. The social actions carried out totaled 160 patient anamnesis records between 2020 and 2023 in Juazeiro- BA and Petrolina- PE. The research reveals the prevalence of young patients, but with a significant number of children and elderly people, from whom data was collected on treatments carried out, treatments that need to be carried out and referrals for emergency cases. In view of this, the importance that integravasf plays in reducing factors that affect oral health in society, especially in vulnerable communities, is clear. The focus on promoting adequate oral health for the population that faces obstacles in accessing this sector due to socioeconomic problems. The role of integravasf is fundamental in the propagation, prevention and recovery of oral cavity health, making it accessible to everyone. This study contributes to understanding the oral health situation in the communities served, reinforcing the importance that the IntegraVasf project plays.